THE IMPLEMENTATION OF A-TOOLIPS, A LEARNING MOBILE APPLICATION FOR DEAF CHILDREN TO PRODUCE WORDS (Jurnal Teknologi (Sciences & Engineering), 2016)
The deaf have a very fundamental problem, which is the ability to communicate and interact, so that it makes their very complicated. In the process of learning in basic education, the problem root faced by children with hearing impairment is the limitation in identifying and producing words. The learning process is limited to only rely on time at the school was an obstacle for them. Therefore, A-TooLips built as learning applications on mobile devices for the deaf children focusing on the ability to produce words. A-TooLips gives more time and places for hearing impaired children to learn, so that it helps their problem in communicating and interacting with others. It is explained in this paper that the A-TooLips has been successfully implemented and tested by some children with hearing impairment, and reached positive results.